Formulation and Evaluation of Herbal Lipstick Containing Saffron as a Natural Colorant - Mouna A; Ashok Kumar BS; Nandeesh R; Lakshman K; Naveen Simon (College of Pharmacy / Mustansiriyah University, 2023)
Ancient peoples were using lipstick which was made by natural sources to protect and to increase the beauty of lips. Herbal lipstick ingredients provide pigments, antioxidants, waxes, oils, fragrance and preservatives. Saffron used to look younger and brighter and also used to treat acne, wounds and skin diseases. The herbal lipstick was formulated by using white bees wax, soft paraffin, coconut oil, almond oil, vanilla essence, orange juice, lemon juice and natural colorant saffron. Formulated lipstick was subjected to evaluation by different parameters like breaking point, softening point, melting point, surface anomalies, aging stability, perfume stability, solubility test and pH. Our formulated showed ideal properties of lipstick like spreading, shining and smoothness of lips after application. It was concluded that this herbal lipstick has better option to women with minimal side effects and further detailed studies are required to assess for better efficacy.